2021
DOI: 10.2478/jped-2021-0004
|View full text |Cite
|
Sign up to set email alerts
|

Getting a risk-free trial during COVID: Accidental and deliberate home educators, responsibilisation and the growing population of children being educated outside of school

Abstract: Numbers coming out of education departments in Australia suggest that, even though most Australian schools are open, and families are able to send their children to them, increasing numbers of parents are deciding to keep their children at home for their education (Queensland Government: Department of Education, 2020). It may be that, as the president of Australia’s home education representative body stated during the pandemic, Covid school closures offered a “risk-free trial” of home education (Lever, 2020) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
8
0
2
Order By: Relevance
“…Educational disruptions experienced during the pandemic might have impacted on children's mental health and families' subsequent decision to de-register from school. Some evidence from data on home schooling (that is, the provision of education at home for a schoolregistered child while schools were closed during the pandemic) indicated mixed experiences in families of children with a neurodevelopmental condition (Greenway and Eaton-Thomas, 2020;Asbury et al, 2021;English, 2021;Ludgate et al, 2021;Wenham et al, 2021). Some parents reported that their children "thrived" during home schooling (Greenway and Eaton-Thomas, 2020;English, 2021;Ludgate et al, 2021).…”
Section: Covid-19 Disruptions To Education and The Mental Health Of C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Educational disruptions experienced during the pandemic might have impacted on children's mental health and families' subsequent decision to de-register from school. Some evidence from data on home schooling (that is, the provision of education at home for a schoolregistered child while schools were closed during the pandemic) indicated mixed experiences in families of children with a neurodevelopmental condition (Greenway and Eaton-Thomas, 2020;Asbury et al, 2021;English, 2021;Ludgate et al, 2021;Wenham et al, 2021). Some parents reported that their children "thrived" during home schooling (Greenway and Eaton-Thomas, 2020;English, 2021;Ludgate et al, 2021).…”
Section: Covid-19 Disruptions To Education and The Mental Health Of C...mentioning
confidence: 99%
“…Some evidence from data on home schooling (that is, the provision of education at home for a schoolregistered child while schools were closed during the pandemic) indicated mixed experiences in families of children with a neurodevelopmental condition (Greenway and Eaton-Thomas, 2020;Asbury et al, 2021;English, 2021;Ludgate et al, 2021;Wenham et al, 2021). Some parents reported that their children "thrived" during home schooling (Greenway and Eaton-Thomas, 2020;English, 2021;Ludgate et al, 2021). In Wenham et al (2021) study parents reported that they were not considering sending their children back to school after the lockdowns were lifted in the United Kingdom and already de-registered their children from school because children's well-being had improved since home schooling.…”
Section: Covid-19 Disruptions To Education and The Mental Health Of C...mentioning
confidence: 99%
“…In Australia, home-schooling is a legal option, and the pandemic has led to an increase in parents opting to home-school (or home educate), particularly for students with special educational needs [4,12]. It has been posited that during the pandemic, parents were provided with an unwitting trial of home-schooling, and paired with potentially negative views of traditional schooling, increasing numbers of parents chose to continue the practice even after schools re-opened [12]. Most students in Australia attend a government or private school (often religious in nature).…”
Section: Home-schooling In Australiamentioning
confidence: 99%
“…Educational disruptions experienced during the pandemic might have impacted on children’s mental health and families’ subsequent decision to de-register from school. Some evidence from data on home schooling (that is, the provision of education at home for a school-registered child while schools were closed during the pandemic) indicated mixed experiences in families of children with a neurodevelopmental condition ( Greenway and Eaton-Thomas, 2020 ; Asbury et al, 2021 ; English, 2021 ; Ludgate et al, 2021 ; Wenham et al, 2021 ). Some parents reported that their children “thrived” during home schooling ( Greenway and Eaton-Thomas, 2020 ; English, 2021 ; Ludgate et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence from data on home schooling (that is, the provision of education at home for a school-registered child while schools were closed during the pandemic) indicated mixed experiences in families of children with a neurodevelopmental condition ( Greenway and Eaton-Thomas, 2020 ; Asbury et al, 2021 ; English, 2021 ; Ludgate et al, 2021 ; Wenham et al, 2021 ). Some parents reported that their children “thrived” during home schooling ( Greenway and Eaton-Thomas, 2020 ; English, 2021 ; Ludgate et al, 2021 ). In Wenham et al (2021) study parents reported that they were not considering sending their children back to school after the lockdowns were lifted in the United Kingdom and already de-registered their children from school because children’s well-being had improved since home schooling.…”
Section: Introductionmentioning
confidence: 99%